Financial development and economic growth based on panel evidence from developed and developing countries - Abdullahi, Abubakar (2012)
The importance of finance on economic growth cannot be underscored and has long being highlighted by existing studies. However, most previous studies are restrictive either to the analysis of banking sector or stock market development on economic growth. By so doing, these studies have failed to capture the full effect of financial development on economic growth. Again, the study of finance-growth nexus is being confronted with the problem of choice of most suitable measure of financial development as each indicator of financial sector development has its merits and demerits. Again, the effect of finance on growth may not apply uniformly across all countries. Also, the debate on the effect of openness on financial sector development is mixed. It is argued that certain pre-conditions are necessary and should precede financial liberalization. One of such argument is the simultaneous opening of trade and capital account as proposed by Rajan and Zingales (2003). This study has two objectives. First is to investigate the role financial development on economic growth and second, to examine the role of trade and capital account openness on financial sector development. In this study, financial development is denoted by the principal components of banking and stock market development. The reason for using principal component is to address multicollinearity problem and also to solve problem of choosing the best measure. The importance of this study to the finance-growth literatures cannot be overemphasized. Firstly, it provides rather a more comprehensive approach to the analysis of finance and growth as it examined the effect of both banking sector and stock market developments on economic growth. Secondly, it addresses the problem of the choice of suitable measure of financial development by constructing the principal components of banking and stock market development. Finally, it probes Rajan and Zingales (2003) postulation by investigating the concurrent liberalization of both trade and capital account. This study utilizes dynamic panel system GMM estimator on data of 53 countries, using annual data from 1990-2009 averaged over five (5) for the first objective and from 1996-2009 averaged over (4) years. GMM is said to be asymptotically efficient under large cross sectional unit and small time series, as in our case. Furthermore, the choice of this estimator owes to its superiority over other dynamic panel estimators in addressing the problems of simultaneity, endogeneity, country-specific effect, etc. The results of first objective suggest that banking sector and stock market development have positive relationship with economic growth. Also, trade openness and investment are found to be statistically significant determinants of growth. Furthermore, the result shows that stock market development is important to growth in developed countries while banking sector development does not matter to growth in developed countries.This confirms financial structure hypothesis. On the other hand, we find banking and stock market development to affect growth in developing countries. For the second objective, the results show that banking sector development, trade openness, and the interaction between trade and capital account openness may affect stock market development positively. The empirical result further reveals that capital account openness may be said to affect stock market development negatively, but the effect of capital account openness may be said to depend on the stage of development. Capital account openness promotes stock market development in developed countries but leads to stock market volatility in developing countries. Finally, we find evidence of negative effect of institutional quality on stock market development. Following our result, we established mixed evidences to the well-known hypothesis of Rajan and Zingales (2003) who stipulate that both trade and capital account openness are necessary for financial sector development to take place.